The Comparison of The Received Doses of Tumoral and Organs at Risk (Spine and Thyroid) between Mixed Photon-Electron Beam Method and Photon Therapy in Supraclavicular Region of Patients with Right Side Breast Cancer that Endure Mastectomy - Fatholah Mohaghegh; Mehran Mohseni; Nasrin Robatmili; Mohamad Reza Bayatiani; Fatemeh Seif; Nayyer Sadat Mostafavi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2018)
Background and Aim: Radiation therapy is the destruction of cancer cells that in all patients with breast cancer reduces tumor recurrence, relieves pain in local tumors and metastases. There are different treatment methods around the world such as electron, photon alone or a combination of both types of fields. Materials and Methods: In this study, photon therapy (PT) and mixed photon-electron therapy (MPET) were used to treat malignancies of the supraclavicular lymph nodes. 30 patients with right-sided breast cancer with local lymph node metastasis were recruited. The ISOgray software was utilized to collect data about treatment planning methods with PT and MPET. Findings: The maximum and mean delivered doses of radiation to the supraclavicular region were 52.08±1.64, 42.59±0.51 Gy and 54.24±1.64, 43.67±0.43 Gy in the PT and MPET methods, respectively. The mean irradiated volumes of supraclavicular fossa that received 90% of the radiation dose were 59.74±1.94% and 70.26±0.94% in the PT and MPET methods, respectively (p=0.004). The maximum doses delivered to the spine were 14.66±1.9 Gy and 10.22±0.92 Gy and the thyroid were 42.62±3.1 Gy and 37.67±5.02 Gy in the PT and MPET methods, respectively. Conclusion: The maximum doses delivered to the spine and thyroid significantly diminished by the novel method. Additionally, supraclavicular region received higher maximum and mean doses in the new treatment modality compared to the conventional methods. The new method improved dose coverage for the tumor.